Right Truncated‏ ‏of mixed Komal-Weibull Distribution with properties - Hamza, Sairan; Atiya Kalaf , Bayda; Rehman, Erum (Journal of Economics and Administrative Sciences, 2024)
Purpose: Truncated distributions occur in many practical situations and predict real phenomena.Theoretical framework: this paper proposed a right-truncated mixed Komal-Weibull distribution on [0,1] with three parameters, and derived some of its properties.approach: To show the ability and behavior of this distribution, some mathematical properties are given, such as the likelihood distribution function, the cumulative distribution function, the reliability function, the hazard function, the properties of the kth moments, the variance, skewness, and kurtosis coefficients, the moment generating function and the distribution of order statistics. In addition, the maximum likelihood estimate is derived.Findings: the new distribution is flexible with the three parameters.Research, Practical & Social Implications: The new distribution has social implications, significant research, and practical. It enhances the ability to model and analyze truncated data accurately.Originality: The right-truncated mixed Komal-Weibull distribution can be used in various fields such as agriculture, medicine, engineering, and physics.